2017
DOI: 10.1038/s41467-017-00348-3
|View full text |Cite
|
Sign up to set email alerts
|

The mTORC1-4E-BP-eIF4E axis controls de novo Bcl6 protein synthesis in T cells and systemic autoimmunity

Abstract: Post-transcriptional modifications can control protein abundance, but the extent to which these alterations contribute to the expression of T helper (TH) lineage-defining factors is unknown. Tight regulation of Bcl6 expression, an essential transcription factor for T follicular helper (TFH) cells, is critical as aberrant TFH cell expansion is associated with autoimmune diseases, such as systemic lupus erythematosus (SLE). Here we show that lack of the SLE risk variant Def6 results in deregulation of Bcl6 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 58 publications
(99 reference statements)
3
57
0
Order By: Relevance
“…Among 564 immune-related transcripts that were screened in this study, only 11 were identified as targets of translational control via 4E-BP1/2 in macrophages. These data are in line with numerous reports, including comparative analyses of the translatomes of WT and 4E-BP1/2 DKO mice and cells (6,52), showing that 4E-BPs do not act as general translational repressors but rather target specific subsets of mRNAs (21,(53)(54)(55)(56)(57)(58)(59). Despite the fact that eIF4E is required for cap-dependent translation of all nuclear-encoded mRNAs, some of them are particularly sensitive to eIF4E levels and/or availability and therefore are referred to as "eIF4E-sensitive" (5,31,32).…”
Section: Discussionsupporting
confidence: 92%
“…Among 564 immune-related transcripts that were screened in this study, only 11 were identified as targets of translational control via 4E-BP1/2 in macrophages. These data are in line with numerous reports, including comparative analyses of the translatomes of WT and 4E-BP1/2 DKO mice and cells (6,52), showing that 4E-BPs do not act as general translational repressors but rather target specific subsets of mRNAs (21,(53)(54)(55)(56)(57)(58)(59). Despite the fact that eIF4E is required for cap-dependent translation of all nuclear-encoded mRNAs, some of them are particularly sensitive to eIF4E levels and/or availability and therefore are referred to as "eIF4E-sensitive" (5,31,32).…”
Section: Discussionsupporting
confidence: 92%
“…Often identified as CXCR5 + PD-1 + CD4 + T cells, Tfh cells are recruited into lymphoid follicles by CXCL13, the ligand for CXCR5, and promote B cell maturation in germinal centers through production of IL-21, CXCL13, IL-4, and CD40L (11). Tfh cells have been observed to be expanded in cohorts of SLE patients (9,10,12,13), and defective regulation of Tfh cells contributes to a lupus-like disease in multiple murine models ( [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to speculate that heat exposure inhibits the proliferation of IECs via the inhibition of protein turnover. mTORC1 is essential for intestinal epithelial homeostasis and regeneration (Laplante & Sabatini, 2012), depending partly on the proliferation and growth process of IECs (Fan et al, 2017;Yi et al, 2017). Previous studies have shown that inhibition of the mTORC1 signaling pathway reduces cell proliferation and blocks regeneration (Gonzalez-Estevez et al, 2012;Guo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%